SUSTAINABLE COFFEE PRODUCTION: THE EFFECT OF SOCIAL NORMS, TRUSTS AND NETWORKS ON COFFEE FARMERS’ADOPTION BEHAVIOR IN LAMPUNG PROVINCE, INDONESIA - Ali, Suprihatin; Wulandari, Christine; Endaryanto, Teguh; Budiono, Pitojo; Tugiono, Tugiono (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Sustainable coffee production is critical for ecological balance and livelihood resilience, yet adoption rates among smallholders remain variable. Although social capital is acknowledged as a key driver of agricultural sustainability, the distinct impacts of its constituent dimension’s norms, networks, and trust are insufficiently understood. This study aims to elucidate the differential influence of these social capital dimensions on sustainable production behavior among coffee farmers in Lampung Province, Indonesia. Employing a cross-sectional quantitative explanatory design, data were gathered via structured surveys from 250 coffee farmers selected through purposive sampling over a two-month period. Measurement instruments adapted from established scales underwent rigorous validation. The structural model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping to ensure robustness. Findings demonstrate that social norms and social networks exert significant positive effects on farmers' adoption of sustainable coffee practices. Conversely, social trust exhibits no direct statistical influence on behavior. The structural model explains a substantial proportion of behavioral variance and demonstrates adequate predictive relevance. This research offers novelty by empirically disentangling the multidimensional nature of social capital in agricultural contexts, challenging the prevailing assumption that all dimensions uniformly drive sustainability outcomes. Theoretically, it advances social capital literature by validating dimension-specific effects within agrarian settings. Practically, implications suggest that extension programs and policymakers should prioritize norm activation through respected community figures and strengthen peer-to-peer knowledge exchange networks. These levers prove more effective for behavioral change than generalized trust-building alone.